Scaling Tennis Racquets During PE in Primary School to Enhance Motor Skill Acquisition. Issue 4 (1st October 2016) - Buszard, Tim; Reid, Machar; Masters, Rich S. W.; Farrow, Damian
Abstract : Purpose: Research supporting the skill acquisition benefits of scaling sports equipment for children in a real-world setting where child-to-coach ratios are high is scarce. Thus, the aim of this study was to examine the influence of scaling the tennis racquet on children's skill acquisition in a primary school setting.Method: Children aged 6 to 7 years old practiced for 5 weeks during physical education classes using either a small racquet (SR group; n = 23) or a large racquet (LR group; n = 23). Measures of hitting technique, hitting performance, and general hand–eye coordination were administered before and after the practice period.Results: The high child-to-coach ratio (22:2) seemingly led to a small number of practice opportunities for children. Despite this finding, children in the SR group displayed greater improvements in hitting technique for the forehand and backhand. This finding did not translate to better hitting performance (i.e., skill outcome), however, with similar results found for both groups during the pretest and posttest. Conversely, the LR group showed greater improvements in the hand–eye coordination measure of bouncing the ball on the ground.Conclusion: Scaling equipment for children enhanced the acquisition of a more desirable technique in a real-world setting. We speculate that this technique acquisition would also lead to improved hitting performance following a longer practice period, whereby children are exposed to more practice opportunities.